Interest Comparison of Music Listeners via the Spotify and Joox Platforms among Students - Simbolon, Nur Anisa; Samura, Laras Hilda; Panjaitan, Novia Adeliana; Rifai, Muhammad; Siregar, Tiur Malasari (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This study aims to determine the comparison of interest of music listeners through Spotify and Joox platforms. The method of research used is a qualitative descriptive method by conducting interviews with several students who use music applications. The results of research conducted from this study can be seen more Spotify application users than the Joox application because Spotify application users more often use the application in the context of studying, doing homework, which is listened to when at home or outside.